Accreditation of prior experiential learning and the development of higher education - Triby, Emmanuel [Verfasser] (My University, 2009)
"This article analyses the specificity of the French accreditation system in higher education as regards lifelong learning. The changes in higher education may thus take on a new significance. The article describes the changes that could come from wider deployment of the system in higher education. The accreditation system introduced in France in 2002 has practically no equivalent in Europe or the world. Many accreditation systems outside France grant conditional access to courses leading to a qualification, especially for graduate training, but only the French system offers the possibility of acquiring a qualification, full or partial, without prior instruction. Against the background of the changes in higher education - particularly its inclusion in a different form of linkage to the needs of economic development - it is interesting to assess what is riding on the introduction of this new right and to try to grasp its current and future implications. To understand the role that the accreditation of prior experiential learning (APEL) could play in the development of higher education, it is important first to establish the nature of this certification system - which for the moment is very typically French - and how it fits in with the possibilities opened up by lifelong learning. Then we need to examine the problems facing higher education today in relation to the questions asked of it by prior learning. It will then be possible to set out the problems that this system could solve, both in France and abroad, provided that certain resistance can be overcome." (Autorenreferat, BIBB-Doku)
Keywords: S 2.2.4.4 Anerkennung non-formaler Qualifikationen; I 2.2.1 Westeuropa; Hochschulbildung; Erfahrungswissen; Anerkennung; Zertifizierung; Lebenslanges Lernen; Frankreich